2021
DOI: 10.1001/jamanetworkopen.2021.31884
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Japanese Centenarians’ and Noncentenarians’ Medical Expenditures in the Last Year of Life

Abstract: IMPORTANCEAlthough research has shown that centenarians tend to experience shorter periods of serious illness compared with other age groups, few studies have focused on the medical expenditures of centenarians as a potential indicator of the scale of medical resources used in their last year of life. OBJECTIVE To compare Japanese centenarians' and noncentenarians' monthly medical expenditures during the year before death according to age and sex. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…The presence of chronic diseases, mainly neoplasms, and cardiovascular and neurodegenerative diseases were identified as significant variables in the descriptive analysis, with centenarians displaying fewer diseases than non-centenarians. These findings are consistent with previous ones found in the analysis of New England long-lived individuals ( 10 ) and Danish ( 34 ) and Japanese centenarians ( 30 ). Interestingly, neoplasms were one of the most relevant variables in both logistic regression and SVM models, with the increase of neoplasms supposing a reduction in the odds of being centenarian.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of chronic diseases, mainly neoplasms, and cardiovascular and neurodegenerative diseases were identified as significant variables in the descriptive analysis, with centenarians displaying fewer diseases than non-centenarians. These findings are consistent with previous ones found in the analysis of New England long-lived individuals ( 10 ) and Danish ( 34 ) and Japanese centenarians ( 30 ). Interestingly, neoplasms were one of the most relevant variables in both logistic regression and SVM models, with the increase of neoplasms supposing a reduction in the odds of being centenarian.…”
Section: Discussionsupporting
confidence: 93%
“…There are a few studies that analyzed the features of centenarians and relate them to human aging. Demographic, socioeconomic, cognitive, functional, and clinical data can be retrieved through the use of questionnaires ( 10 , 12 , 29 ), which usually focus on the assessment of vital and behavioral status or the analysis of medical expenditures ( 30 ). However, the number of studies that provide a complete picture of centenarians' profiles based on healthcare records is very scarce ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Jonckheere-Terpstra test generates standardized statistics (SS) that point to the strength of tendencies in variables that increase or decline across groups. [26][27][28] We applied logistic regression to evaluate the obesity-and sex-specific associations between the TyG index and MS CKD. The fully adjusted model was adjusted for potential confounders such as education level, household income, smoking, drinking, handgrip strength, moderate-to-vigorous physical activity, total energy intake, and BMI, which are recognized or suspected factors associated with CKD.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Tai et al 2021 [ 8 ] showed that centenarians with lower calf circumference were associated with an increased risk of cognitive impairment, and underweight women were predisposed to cognitive impairment [ 5 ]. However, there is wide variation in the currently available data [ 9 , 10 ]. Management of centenarians and older adults differs considerably according to settings (e.g., hospital vs. residential), and strategies to improve muscle mass, muscle function, and quality of life (QOL) in this population have been investigated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%